A reproducible, high throughput method for fabricating fibrin gels - Murphy, Kaitlin C (BioMed Central, 2012)
BACKGROUND: Fibrin gels are a promising biomaterial for tissue engineering. However, current fabrication methods are time intensive with inherent variation. There is a pressing need to develop new and consistent approaches for producing fibrin-based hydrogels for examination. FINDINGS: We developed a high throughput method for creating fibrin gels using molds fabricated from polydimethylsiloxane (PDMS). Fibrin gels were produced by adding solutions of fibrinogen and thrombin to cylindrical defects in a PDMS sheet. Undisturbed gels were collected by removing the sheet, and fibrin gels were characterized. The characteristics of resulting gels were compared to published data by measuring compressive stiffness and osteogenic response of entrapped human mesenchymal stem cells (MSCs). Gels exhibited compressive moduli nearly identical to our previously reported fabrication method. Trends in alkaline phosphatase activity, an early marker of osteogenic differentiation in MSCs, were also consistent with previous data. CONCLUSIONS: These findings demonstrate a streamlined approach to fibrin gel production that drastically reduces the time required to make fibrin gels, while also reducing variability between gel batches. This fabrication technique provides a valuable tool for generating large numbers of gels in a cost-effective manner.